(untitled) (Development Service Industry Management, 2025)
The article addresses the urgent challenge of enhancing management efficiency in Ukrainian healthcare organizations amid systemic transformations in the national health system. The study emphasizes the necessity of adopting innovative approaches to organizational activities in order to adapt to increasing patient expectations and to optimize the use of limited resources. The paper explores the potential of operational optimization and improvement of healthcare service quality through the implementation of modern managerial tools, particularly those based on process-oriented management and business process reengineering. The relevance of these approaches for the healthcare sector is justified by referencing academic research demonstrating the effectiveness of business process management in clinical settings. Drawing on statistical data from the National Health Service of Ukraine (NHSU), the article highlights the significant impact of inefficient internal processes on the financial stability and service quality of medical institutions. Examples from Ukrainian hospitals demonstrate both the limitations of outdated administrative structures and the positive outcomes of implementing digital solutions, such as medical information systems, which reduced paperwork and improved coordination. The research systematizes key business processes in medical organizations—including patient registration, diagnostics, treatment, logistics, administration, and quality management—while analyzing their interdependencies and identifying bottlenecks. The study stresses the importance of addressing functional fragmentation, communication gaps, insufficient standardization, and limited digitalization as primary barriers to efficiency. It further explores the role of bifurcation changes and adaptability in healthcare management, arguing that proactive strategies, continuous monitoring, and the cultivation of resilience are crucial for overcoming systemic challenges. The novelty of the article lies in articulating underexplored aspects of business process management in the specific context of Ukrainian healthcare, with an emphasis on synergetic integration, stakeholder interaction, and adaptability to bifurcation-driven transformations. Practical recommendations include expanding digitalization, enhancing interfunctional coordination, investing in staff training, and standardizing clinical protocols. By adopting a systemic, process-based approach, Ukrainian medical institutions can improve financial stability, ensure sustainable development, and achieve higher quality of healthcare services.